The Differentiation and Protective Function of Cytolytic CD4 T Cells in Influenza Infection - Brown, Deborah M.; Lampe, Anna T.; Workman, Aspen M. (Frontiers in Immunology, 2016)
CD4 T cells that recognize peptide antigen in the context of Class II MHC can differentiate into various subsets that are characterized by their helper functions. However, increasing evidence indicates that CD4 cells with direct cytolytic activity (CD4 CTL) play a role in chronic, as well as, acute infections such as influenza A virus (IAV) infection. In the last couple of decades, techniques to measure the frequency and activity of these cytolytic cells has demonstrated their abundance in infections such as HIV, mouse pox, murine gamma herpes virus, CMV, EBV and influenza among others. We now appreciate a greater role for CD4 CTL as direct effectors in viral infections and anti-tumor immunity through their ability to acquire perforin mediated cytolytic activity and contribution to lysis of virally infected targets or tumors. As early as the 1980s, CD4 T cell clones with cytolytic potential were identified after influenza virus infection, yet much of this early work was dependent on in vitro culture and little was known about the physiological relevance of CD4 CTL. Here, we discuss the direct role CD4 CTL play in protection against lethal IAV infection and the factors that drive the generation of perforin mediated lytic activity in CD4 cells in vivo during IAV infection. While focusing on CD4 CTL generated during IAV infection, we pull comparisons from the literature in other anti-viral and anti-tumor systems. Further, we highlight what is currently known about CD4 CTL secondary and memory responses, as well as vaccination strategies to induce these potent killer cells that provide an extra layer of cell mediated immune protection against heterosubtypic IAV infection.